Effects of resistance training on performance in previously trained endurance runners: A systematic review - Alcaraz-Ibañez, M.; Rodriguez-Pérez, M. (Journal of Sports Sciences, 2018)
The aim of this work was to identify, synthesize and evaluate the results of randomized controlled trials examining the effects of resistance training on performance indicators in previously trained endurance runners. A database search was carried out in PubMed, Science Direct, OvidSPMedLine, Wiley, Web of Science, ProQuest and Google Scholar. In accordance with the PRISMA checklist, 18 published articles dated prior to May 2016 involving 321 endurance runners were reviewed using the PEDro scale. Resistance training led to general improvements in muscular strength, running economy, muscle power factors, and direct performance in distances between 1,500 and 10,000 m. Such improvements were not accompanied by a significant increase in body mass or signs of overtraining. However, improvements did not occur in all cases, suggesting that they might depend on the specific characteristics of the resistance training applied. Although current evidence supports the effectiveness of resistance training to improve performance in already trained endurance runners, the methodological inconsistencies identified suggest that the results should be interpreted with caution. Future studies ought to investigate the benefits of resistance training in endurance runners while considering the existence of possible differentiated effects based on the specific characteristics of the resistance training carried out.